Stunting Literacy Strategy of the Library and Archives Office: Increasing Public Awareness and Understanding - Fahri, Muhammad Syahruddin; Sayekti, Retno (Newinera Publisher, 2024)
The purpose of this research is to provide a detailed explanation of the stunting literacy approach implemented by the Labuhanbatu Utara Regency Library and Archives Office to increase public awareness and understanding of stunting. This research uses qualitative analysis using the Miles and Huberman paradigm to gain insight into the librarian's point of view. Data were collected through interviews, observation, and documentation. The Library and Archives Office of Labuhanbatu Utara Regency implemented various initiatives aimed at increasing public understanding and awareness of stunting. These activities include improving literacy collection development by offering a variety of library materials, fostering partnerships with related organizations, and providing access to Online Public Access Catalog (OPAC) services. Working with BKKBN, the Health Office, academics and health workers. Social promotion and campaign: Involves disseminating information through several media channels and organizing social campaigns. Devotion of local government Collaboration between various agencies Compilation of extensive literacy resources to address stunting. To achieve success, it is crucial to have active involvement and support from community members and leaders. Barriers Limited resources Limited availability of information Lack of collaboration among government organizations Recommendations Increase collaboration and synchronization among agencies Increase availability of information Improve librarian skills Conduct program monitoring and evaluation Conclusion Labura district has made great strides in improving understanding of stunting. These efforts deserve recognition and are expected to be continuously improved to achieve the goal of reducing stunting rates in Labuhanbatu Utara Regency.